Commitment to environmental protection in accordance with the provisions of petroleum licensing contracts - المالكي, د. رائد حمدان (Journal of Petroleum Research and Studies, 2021)
The terms and provisions contained in the petroleum licensing rounds (service contracts) are representing the foundation for the commitment of the parties concerned to protect the environment through pollution prevention, treating its damages in addition to the removal or reduction of their effects. The aim of this study is to identify the provisions contained in the contracts of petroleum licensing rounds on the protection of the environment and its effectiveness, as well as legislative texts in achieving the goal of the state and its commitment to prevent environmental damages